Macroeconomic Strest Testing terhadap Risiko Kegagalan Perbankan di Indonesia - Fitrotul Fardila; Muhammad Rudi Nugroho (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
The economic crisis that hit Indonesia in 1998 had a negative impact on the stability of the Indonesian economy, including the banking sector. The banking sector as the coffers that drain funds to all sectors of the economy cost the restructuring is not small. The stress test is a method used to measure the stability of the financial system through the calculation of credit risk. In addition, stress tests can provide information about the nature of the financial system in crisis conditions and assist policymakers in calculating the level of financial system vulnerabilities. So that if the vulnerability of the financial system can be detected early, the government can take preventive measures to minimize the consequences. Thus, this study aims to examine the effect of macroeconomic variable shock on the probability of default of conventional banking and sharia banking in Indonesia through a logistic regression method. The probability of default occurrence as the dependent variable in this study is determined by using the credit failure ratio. While the independent variables used in this study are macroeconomic variables consisting of growth variables Gross Domestic Product (GDP), Exchange rate, inflation, and IHSG. The result of this research using the data of period 1st quarter of 2006 to 3rd quarter of 2017 concludes that IHSG is chosen as the main variable in forming stress test scenario. Based on the results of macroeconomic stress tests, great shock on IHSG holds the most significant change to the possibility of a banking default. By using the curve-fitting method, it is known that Syariah Rural Bank (BPRS) has the greatest possibility of default when shock occurs on IHSG variables compared to 8 other banks. Keywords: Probability of Default, Stress Test, Macroeconomic Stress Testing, Financial Stability